Online monitoring of biomass concentration with the biO2mass sensor technology - Stempin, I.; Kovacs, Z.; Czermak, Peter (My University, 2014)
In situ measurement of biomass is one of the most critical analytical procedures in biotechnological processes. In our laboratory, we have developed a sensor, called biO2mass sensor (Patent No DE 10 2013 006 972.6), for measuring biomass concentration of aerobic cultures during fermentation. The principle of the measurement is based on periodically creating a small, enclosed sampling room in the fermenter in which the rate of decay in dissolved oxygen correlates with the actual biomass concentration. The applicability of the proposed technique is proven by experimental investigations on fermentation processes using various strains such as Pichia pastoris and Escherichia coli K 12. The obtained data from the biO2mass sensor shows excellent correlation with dry cell weight and optical density measurements. This simple procedure allows a rapid, sensitive, cheap, in situ measurement of the concentration of living aerobic cells.
Keywords: Bioprocess monitoring; Biomass; In situ; On-line; Sensors; Optode